Asymmetric and enantiospecific syntheses of 1-hydroxymethyl pyrrolizidine alkaloids - Brambilla, M; Davies, S; Fletcher, A; Thomson, J (Elsevier, 2014)
Isoretronecanol and trachelantamidine (laburnine) are naturally occurring pyrrolizidine alkaloids which display potent biological activity, and as such these compounds have, in recent years, attracted significant interest from the bioorganic and synthetic communities. This review delineates both the asymmetric and enantiospecific syntheses of 1-hydroxymethyl pyrrolizidine alkaloids including isoretronecanol, trachelantamidine (laburnine) and related hydroxylated compounds. © 2014 Elsevier Ltd. All rights reserved.